2020
DOI: 10.1155/2020/8860467
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salivary and Serum Total Antioxidant Capacity and Lipid Peroxidation in Postmenopausal Women

Abstract: Objective. In menopause, reduction of estrogen hormone affects oxidative stress process in serum. Oxidative stress in saliva plays a significant role in the pathogenesis of oral diseases. The aim of this study was to investigate the total antioxidant capacity and lipid peroxidation in the serum and saliva of premenopausal and postmenopausal women. Methods. In this case control study, 50 postmenopausal women (case group) and 48 premenopausal women (control group) were selected. The unstimulated whole saliva and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…In previous studies, postmenopausal women [ 42 ] and hypertensive individuals [ 43 ] had lower FRAP values, demonstrating the presence of oxidative damage. The ferric-reducing ability of plasma, FRAP, has been used as an indirect measurement to determine the total antioxidant activity, and some studies have shown high values of this marker in patients with one or more morbidity such as hypertension, obesity, diabetes, and metabolic syndrome [ 44 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous studies, postmenopausal women [ 42 ] and hypertensive individuals [ 43 ] had lower FRAP values, demonstrating the presence of oxidative damage. The ferric-reducing ability of plasma, FRAP, has been used as an indirect measurement to determine the total antioxidant activity, and some studies have shown high values of this marker in patients with one or more morbidity such as hypertension, obesity, diabetes, and metabolic syndrome [ 44 ].…”
Section: Discussionmentioning
confidence: 98%
“…In postmenopausal women, the reduction in 17β-estradiol directly impacts aspects of mitochondrial function, including the production of ROS and ATP, and the membrane potential [ 48 ]. Considering that cardiometabolic diseases and the climacteric are associated with oxidative stress, these women probably started the exercise protocol under higher oxidative stress [ 8 , 42 , 49 , 50 , 51 , 52 ]. There is a lack of research investigating the effects of the Pilates method on redox status; therefore, given that this method has some characteristics similar to resistance and/or isometric training method, we can compare our results with studies using those types of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The mean FRAP TAC obtained from our healthy controls was somewhat lower than these; 881.8±104.7 μmol/L, but higher than the FRAP TAC obtained among healthy premenopausal Iranian women; 846.04 ± 152.56 μmol/L [33]. Of note however, was that our screening for health status applied in the recruitment of the control group was essentially limited to exclusion based on information obtained from history taking as indicated in the methodology section.…”
Section: Discussionmentioning
confidence: 54%
“…Our findings were in agreement with the studies of Dikker, et al 25 (Corum and Istanbul, Turkey) and Klisic et al 23 (Montenegro and Serbia). However; Altindag et al 22 (Sanliurfa, Turkey), Zovari, et al 26 (Babol, Iran), Bednarek-Tupikowski, et al 27 (Wroclaw, Poland), and Kolesnikova et al 28 (Irkutsk, Russia) have found that serum TAS levels were significantly decreased in postmenopausal women. A decreased serum TAS activity is also reported in the review by Zhao, et al 24 The reason for these differences might be related to various conditions such as dietary habits, milieu, regional variations, or hereditary specifications.…”
Section: Tas Level In Postmenopausal Versus Fertile Women (H 02 )mentioning
confidence: 99%